Agroecosystems to decrease diffuse nitrogen pollution in Northern Lithuania - Masilionytė, Laura; Maikštėnienė, Stanislava; Velykis, Aleksandras; Satkus, Antanas (Journal of Environmental Engineering and Landscape Management, 2014)
The paper presents the research conducted at the Joniškėlis Experimental Station of the Lithuanian Research Centre for Agriculture and Forestry on a clay loam Gleyic Cambisol during the period of 2006–2010. The research investigated the changes of mineral nitrogen in soil growing catch crops during the winter wheat post-harvest period and incorporating their biomass into the soil for green manure. Green manure implications for environmental sustainability were assessed. The studies were carried out in the soil with a low (1.90–2.00%) and moderate (2.10–2.40%) humus content in organic and sustainable cropping systems. The crop rotation, expanded in time and space, consisted of red clover (Trifolium pretense L.) → winter wheat (Triticum aestivum L.) → field pea (Pisum sativum L.) → spring barley (Hordeum vulgare L.) with undersown red clover. Investigations of mineral nitrogen migration were assessed in the crop rotation sequence: winter wheat + catch crops → field pea. Higher organic matter and nitrogen content in the biomass of catch crops were accumulated when Brassisaceae (white mustard, Sinapis alba L.) was grown in a mixture with buckwheat (Fagopyrum esculentum Moench.) or as a sole crop, compared with oilseed radish (Raphanus sativus var. Oleiferus Metzg.) grown with the long-day legume plants blue lupine (Lupinus angustifolius L.). Mineral nitrogen concentration in soil depended on soil humus status, cropping system and catch crop characteristics. In late autumn there was significantly higher mineral nitrogen concentration in the soil with moderate humus content, compared with soil with low humus content. The lowest mineral nitrogen concentration in late autumn in the 0–40 cm soil layer and lower risk of leaching into deeper layers was measured using organic cropping systems with catch crops. The highest mineral nitrogen concentration was recorded in the sustainable cropping system when mineral nitrogen fertilizer (N30) was applied for winter wheat straw decomposition. In the organic cropping system, the incorporation of catch crop biomass into soil resulted in higher mineral nitrogen reserves in soil in spring than in the sustainable cropping system, (mineral nitrogen fertilizer (N30) applied for straw decomposition in autumn and no catch crop grown). Applying organic cropping systems with catch crops is an efficient tool to promote environmental sustainability.First published online: 15 May 2014